2014
DOI: 10.5551/jat.25775
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori—An Infectious Risk Factor for Atherosclerosis?

Abstract: Accumulating evidence implicates Helicobacter pylori (H. pylori) infection in the pathogenesis of certain diseases localized outside the stomach, particularly those characterized by persistent and lowgrade systematic inflammation. Recently, the role of H. pylori infection in the development of atherosclerosis and its clinical complications has received attention. Atherosclerosis is a high-cost disease, and acute events resulting from this condition rank first among morbidity and mortality statistics in most in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 136 publications
(108 reference statements)
0
35
1
5
Order By: Relevance
“…Accumulated evidence has suggested that this infection is associated with metabolic diseases, such as metabolic syndrome (Chen et al, 2015a, Chen et al, 2015b), type 2 diabetes mellitus (T2DM) (He et al, 2014b) and atherosclerotic diseases (He et al, 2014a), yet the underlying mechanism is obscure. Insulin resistance (IR) and subsequent hyperinsulinemia are the key pathogenic factors contributing to these metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated evidence has suggested that this infection is associated with metabolic diseases, such as metabolic syndrome (Chen et al, 2015a, Chen et al, 2015b), type 2 diabetes mellitus (T2DM) (He et al, 2014b) and atherosclerotic diseases (He et al, 2014a), yet the underlying mechanism is obscure. Insulin resistance (IR) and subsequent hyperinsulinemia are the key pathogenic factors contributing to these metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Because separate analyses for subjects measured using either J-HM-CAP or E-Plate ELISA kits showed similar results, we chose to combine data sets derived from the two ELISA tests. Of multiple mechanisms proposed to explain the H. pylori infection -CVD associations 15,22) , the effect of H. pylori colonization on atherosclerosis through the generation of a persistent low-grade inflammatory stimulus is plausible. This is because previous studies provided indirect evidence that serum lipid or inflammatory biomarkers such as CRP were significantly higher in H. pylori-infected individuals compared with H. pylori-negative individuals [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…[27], объединивший 26 исследований случай-контроль, продемонстрировал, что инфекция H. pylori ассоциирована с повышенным риском развития инфаркта мио-карда (ОШ 2,10 при 95% ДИ от 1,75 до 2,53; р=0,06). С учетом того, что ДНК H. pylori нередко определяется в атеросклеротиче-ских бляшках, существует гипотеза, что данный микроорганизм может участвовать в процессе атеросклероза, однако доказатель-ных данных в этом направлении пока недостаточно [28].…”
Section: терапевтический архив 8 2015unclassified